Marketing Strategy of Kopi Sejati Products Using SWOT, Marketing Mix 4P, and Boston Consulting Group (BCG) Matrix - Agnes Vicky; Andi Velahyati Baharuddin; Dewi Dewi (Institut Teknologi Dirgantara Adisutjipto, 2026)
Kopi Sejati is a micro, small, and medium enterprise (MSME) in Makassar engaged in the production and sale of locally roasted coffee. Its marketing activities remain limited, relying mainly on exhibitions and direct sales by the owner, with minimal utilization of digital platforms. This study aims to formulate an effective marketing strategy through the integration of SWOT analysis, Marketing Mix (4P), and the Boston Consulting Group (BCG) Matrix. The research employs a descriptive qualitative and quantitative approach, with data obtained from observation, interviews, questionnaires, and sales documentation from 2023–2024.The findings indicate that the most suitable strategy for Kopi Sejati is the Strength–Opportunity (SO) strategy, with total IFAS and EFAS scores of 4.20 and 4.22, placing the business in Quadrant I (aggressive growth strategy). The BCG Matrix identifies Kopi Sejati as a Cash Cow, with a relative market share of 1.25 and an industry growth rate of 4.2%, reflecting a strong yet stable position. The Marketing Mix (4P) analysis highlights product quality and competitive pricing as strengths, while promotion and distribution require improvement. Strengthening digital marketing, forming a dedicated marketing team, and expanding distribution networks are projected to increase market reach by 30% and boost sales by at least 20% annually.